Moral norms, moral ideals and supererogation - Machura, Piotr (Folia Philosophica, 2011)
The aim of the paper is to investigate into the relations between basic moral categories, namely those of norms, ideals and supererogation. I discuss, firstly, the ways of understanding these categories, secondly, how moral acting can be described using them and thirdly, how they relate within certain moral system. Yet, what is of a special importance is the relation between norms and ideals and their complementary character. For it might be argued that omission of one these categories may lead to posing important limitations on the possibilities of grasping certain moral issue adequately (on a descriptive level) and setting the full range of possible solutions (on normative level). Hence, I argue that to resign from two-level form of moral analysis may lead to the atrophy of the very idea of ethics itself.